Kecerdasan Spiritual Sebagai Prediktor Resiliensi Akademik: Analisis Regresi Siswa SMP Mumtaza Islamic School - Tsara Karamah Hutomo; Siti Rohmah (Journal of Education, Humaniora and Social Sciences (JEHSS), 2026)
This study is motivated by the increasing academic stress among adolescents, which affects motivation, concentration, and students’ mental resilience. This condition emphasizes the importance of academic resilience as an adaptive ability in dealing with learning pressures. The study aims to analyze the effect of spiritual intelligence on the academic resilience of Islamic-based middle school students, which remains relatively underexplored in inferential quantitative research. A quantitative approach with a simple regression design was employed. The subjects were 62 eighth-grade students of Mumtaza Islamic Junior High School. The analysis results showed that spiritual intelligence significantly influences academic resilience. These findings confirm the role of spiritual intelligence as an important predictor in enhancing students’ perseverance, psychological resilience, and ability to cope with academic pressure. The study contributes to strengthening the perspective of Islamic educational psychology, particularly in positioning spiritual intelligence as a strategic factor in developing academic resilience. Practically, the results can serve as a basis for schools and educators to integrate spiritual intelligence development into character building and academic guidance.